Using effective medium theories to design tailored nanocomposite materials for optical systems - Werdehausen, Daniel; Staude, Isabelle; Burger, Sven; Petschulat, Joerg; Scharf, Toralf; Pertsch, Thomas; Decker, Manuel (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
Modern optical systems are subject to very restrictive performance, size and cost requirements. Especially in portable systems size often is the most important factor, which necessitates elaborate designs to achieve the desired specifications. However, current designs already operate very close to the physical limits and further progress is difficult to achieve by changing only the complexity of the design. Another way of improving the performance is to tailor the optical properties of materials specifically to the application at hand. A class of novel, customizable materials that enables the tailoring of the optical properties, and promises to overcome many of the intrinsic disadvantages of polymers, are nanocomposites. However, despite considerable past research efforts, these types of materials are largely underutilized in optical systems. To shed light into this issue we, in this paper, discuss how nanocomposites can be modeled using effective medium theories. In the second part, we then investigate the fundamental requirements that have to be fulfilled to make nanocomposites suitable for optical applications, and show that it is indeed possible to fabricate such a material using existing methods. Furthermore, we show how nanocomposites can be used to tailor the refractive index and dispersion properties towards specific applications.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Dispersion engineering; Effective medium theory; Mie theory; Nanocomposites; Nanomaterials; Optical design; Optical materials; Optical Systems